HUBUNGAN ANTARA PERSEPSI KEPEMIMPINAN MANAGER DENGAN KOMITMEN AFEKTIF KARYAWAN KOKAPURA AVIA - Dedy Susanto (JURNAL MANAJEMEN, 2013)
The study was conducted with the aim of knowing the empirical correlation or relationship between perception of manager leadership with employee affective commitment. Methods of data collection in this study using a scale consisting of affective commitment and leadership perception manager. This study was conducted with employees Kokapura Avia total population of 215 people, with 60 employees who have worked a minimum of 1.5 years as a sample and has minimum education senior high school. Sampling technique using proportional sampling method. Based on the results obtained from the correlation test showed that there is a positive and significant relationship between perceived leadership manager and employee affective commitment . Kokapura Avia Yogyakarta is indicated by the calculated correlation coefficient r = 0.618 with a significance level of p = 0.000 correlation. This means that the more positive employee perceptions of manager leadership, the higher employee's commitment to the company where he worked. Keywords: Employee Affective Commitment, Perceptions, Manager Leadership